Cost-Effectiveness Analysis of Results-Based Financing Programs : A Toolkit - Shepard, Donald (World Bank, Washington, DC, 2015)
Results-based financing (RBF), which rewards providers, users, or administrators of services upon achieving a set of verified results, has been gaining attraction in global health as a prominent approach to gain value for money. With a large number of countries adopting RBF in the recent years, evidence starts to emerge which points to the effectiveness of RBF in improving coverage and quality of important services, such as maternal and child health and reproductive health. The current toolkit aims to support country programs to assess the cost-effectiveness of RBF interventions and to facilitate cross-country comparisons of RBF programs. The toolkit is specifically tailored to supply-side RBF but its general principles apply to most health systems interventions directed at the health-related millennium development goals (MDGs). The development of the toolkit was based on actual experience of conducting a cost effectiveness analysis of Zambia’s RBF program and an extensive review of RBF programs features across the health results innovation trust fund (HRITF) portfolio. Given that RBF programs in the HRITF portfolio are typically complex health system interventions, the toolkit recommends a practical approach of adopting a program implementer’s perspective and presents different options for cost-effectiveness analysis (for selected key indicators or for an entire package of services). It also provides guidance on incorporating quality of care, which is strongly emphasized across many RBF programs.